Tele‐manufactured affordable smartphone anterior segment microscope. (12th June 2016) - Chiong, Hong Sheng; Fang, Joyce Lim Luann; Wilson, Graham
Abstract : The recent advances in mobile technology have made the smartphone a powerful and accessible tool. This article describe the development of a novel smartphone‐based anterior segment microscope that is compatible with tele‐manufacturing. The anterior segment microscope is equipped with both cobalt‐blue and red‐free filters that can be used for clinical photo‐documentation. The digital files of the microscope are transferrable and compatible with additive‐manufacturing. Therefore, the entire device can be locally manufactured with rapid prototyping techniques such as 3D printing.